The Development of Nursing Care Services Model for Low Birth Weight Infants - Dessie Wanda; Yeni Rustina; Happy Hayati; Fajar Tri Waluyanti (Jurnal Ners, 2014)
Introduction: Low birth weight (LBW) infants deal with various problems during transitional period from intra-uterine and extra-uterine because of immature organs’ functions. This leads to LBW as the second death cause in Indonesia, particularly in the fi rst seventh days of infants’ lifes. The problem continues to occur at home when the infants have discharged. This research was aimed to develop the nursing care services model for LBW infants and to test the model.Method: The research design was an action research using quantitative and qualitative approach. This design was chosen as it facilitated improvement in health care system, which was involving nurses and other health providers.Results: Nursing care services provided by the nursing team are hindered by several factors, such as various level of nurses’ knowledge, not optimal health education activities, incomplete standard operational procedure, ethical dilemma, paramedic functions, and documentation system. This model was developed based on conservation and becoming a mother/maternal role attainment theory, family-centered care principles, and input from the experts through focus group discussion.Conclusion: The result of this research is going to increase the quality of nursing care for LBW infants by achieving nurses’ and parents’ satisfaction in giving care for their infants which can lead to lower infant death rate.